SOCIAL RESPONSIBILITY IN AQUARIUM BUSINESS: ECONOMIC AND PEDAGOGICAL ASPECTS (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. The cooperation of Ukrainian aquarium business with educational institutions, the desire to develop students' environmental awareness through interactive forms of education form the relevance of the research topic.The purpose of the article. The purpose of the article is to study theoretical and practical principles of economic and pedagogical aspects of aquarium business social responsibility, to formulate recommendations for improvement and priorities of development of socially responsible approach in aquarium segment of economy.Results. The article deals with economic and pedagogical aspects of social responsibility of aquarium business in Ukraine. The evolution of the concept of "social responsibility" is investigated, the domestic and foreign definitions of this scientific category are analyzed, the own vision of economic and pedagogical aspects of social responsibility of aquarium business is formed. The value of social responsibility of aquarium business for creation in educational establishments of the corresponding educational and material base: nature study corner, offices of aquarium is substantiated.According to the results of the research, it is defined that interactive forms and methods of training in aquarium business, including giving master classes, competitions for children and youth in aquaristics and the art of aquadesign contribute to the formation of personality ecological culture, development of cognitive activity more than traditional forms and methods of teaching; teach pupils and students the ability to express and argue their opinions; teach valuable quality - to be able to listen to each other, to act as a critic; contribute to the mastery of fundamental environmental knowledge; form beliefs; learn to predict the effects of anthropogenic impact; model possible environmental situations; call for vigorous environmental activities.\Conclusions. The priority areas for the development of the social responsibility of the aquarium business include: sponsorship and charitable assistance in creating in the educational institutions an appropriate educational and material base: place of wildlife, aquarium rooms, etc.; improving the forms and methods of pupils and students environmental education; active involvement of representatives of aquarium brands in cooperation with schools, institutions of additional education and universities on conducting lectures, presentations, seminars, trainings, master classes, children's and youth competitions in aquarium and aquadesign; the formation of motives for a responsible attitude to nature, the desire to learn more about it, to increase its wealth.
Keywords: business social responsibility, interactive forms of environmental education, aquadesign